Exponential decay of harmonic $1$-forms for wild harmonic bundles on curves - Szabó, Szilárd (Comptes Rendus. Mathématique)
We give a slightly reorganized exposition of the proof of the exponential decay result of T. Mochizuki for harmonic $1$-forms for wild harmonic bundles on a disc.